2015
DOI: 10.1093/gastro/gov016
|View full text |Cite
|
Sign up to set email alerts
|

A rare case of infectious colitis

Abstract: Methicillin-resistant Staphylococcus aureus (MRSA) is responsible for numerous infectious processes. Gastrointestinal tract involvement is rather rare and only a handful of cases of MRSA colitis have been reported in North America. We present a case of MRSA colitis in an adult without apparent risk factors. Abdominal computed tomography (CT) showed thickening of the sigmoid colon, indicative of colitis, and empiric therapy with ciprofloxacin and metronidazole was started. Initial work-up for infection—includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 13 publications
2
9
0
Order By: Relevance
“…A French study on foods incriminated in SFP outbreaks revealed two MRSA strains of the 33 strains tested (K erouanton et al 2007); compared to human clinical isolates, the SFP outbreak strains were more susceptible to antibiotics (except for two SFP outbreak strains that were resistant to methicillin). More recently, a rare case of MRSA colitis in an adult (without any apparent predisposing medical condition) has been reported in the United States (Kalakonda et al 2015). This was the sixth reported case of MRSA colitis in the literature since 1993 (Kalakonda et al 2015).…”
Section: Staphylococcal Enterotoxins and Staphylococcal Food Poisoningmentioning
confidence: 87%
See 3 more Smart Citations
“…A French study on foods incriminated in SFP outbreaks revealed two MRSA strains of the 33 strains tested (K erouanton et al 2007); compared to human clinical isolates, the SFP outbreak strains were more susceptible to antibiotics (except for two SFP outbreak strains that were resistant to methicillin). More recently, a rare case of MRSA colitis in an adult (without any apparent predisposing medical condition) has been reported in the United States (Kalakonda et al 2015). This was the sixth reported case of MRSA colitis in the literature since 1993 (Kalakonda et al 2015).…”
Section: Staphylococcal Enterotoxins and Staphylococcal Food Poisoningmentioning
confidence: 87%
“…More recently, a rare case of MRSA colitis in an adult (without any apparent predisposing medical condition) has been reported in the United States (Kalakonda et al . ). This was the sixth reported case of MRSA colitis in the literature since 1993 (Kalakonda et al .…”
Section: Antimicrobial Resistance Of Food Pathogens: the Case Of Mrsamentioning
confidence: 97%
See 2 more Smart Citations
“…Although several recent reports have indicated a slight decline in CACC incidence in IBD patients [ 7 , 8 ], which might be attributed to the widespread use of 5-aminosalicylic acid and immunosuppressive drugs [ 9 , 10 ], as well as to widespread endoscopic screening and early coloproctectomy, current guidelines continue to recommend a regular surveillance for early detection [ 11 ]. Moreover, because of worse prognosis and higher mortality in CACC than in sporadic CRC [ 12 ], early CACC detection is crucial. Colonoscopy is primarily recommended for surveillance; however, newer technologies and approaches, such as molecular biomarkers in different biosamples, have emerged and the best approach and technique for surveillance remain under debate.…”
Section: Introductionmentioning
confidence: 99%